Diagnóstico de Seguridad Industrial y Salud Ocupacional en los Asaderos Restaurantes de la ciudad de Portovelo, provincia de El Oro. Propuesta de un manual de Seguridad y Salud Ocupacional para el Asadero Restaurante RDH - Suárez Guevara, Sonia Gabriela (2021)
The present research work entitled "Diagnosis of Industrial Safety and Occupational Health in Grills Restaurants of the city of Portovelo, province of El Oro. Proposal of an Occupational Safety and Health manual for the RHD grill restaurant" has the general objective of diagnosing the occupational health and safety in barbecue restaurants in the city of Portovelo, province of El Oro and the proposal of an occupational health and safety manual for the RHD barbecue restaurant and, as specific objectives, carry out a diagnosis regarding the current safety and security situation. occupational health; identify the most incidental occupational risk factors and the working conditions that give rise to occupational diseases in workers; and prepare the occupational health and safety manual for the RHD grill restaurant. Inductive, deductive, analytical and descriptive methods, direct observation techniques, surveys of 17 workers and 7 checklists applied to the owners of the barbecue pits were used to carry out the research. The results of these instruments showed the risks of greater exposure due to their work activity, the knowledge regarding safety is partial, that the workers have not carried out emergency drills or received training, and that currently no grill in the city has a manual of security. This information made it possible to diagnose the current situation of the grills and to prepare the manual. At the end of the investigation, the identification of the main risk factors for the workers was concluded and it is recommended that the barbecue provide the necessary resources for the application of the manual as well as its socialization with the other barbecue facilities in the city.